A proximal enhancer regulates RORA expression during early human Th17 cell differentiation - Kalim, Ubaid Ullah; Biradar, Rahul; Junttila, Sini; Khan, Mohd Moin; Tripathi, Subhash; Khan, Meraj Hasan; Smolander, Johannes; Kanduri, Kartiek; Envall, Tapio; Laiho, Asta; Marson, Alexander; Rasool, Omid; et al. (Academic Press, 2025)
Gene regulatory elements, such as enhancers, greatly influence cell identity by tuning the transcriptional activity of specific cell types. Dynamics of enhancer landscape during early human Th17 cell differentiation remains incompletely understood. Leveraging ATAC-seq-based profiling of chromatin accessibility and comprehensive analysis of key histone marks, we identified a repertoire of potential enhancers that potentially exert control over the fate specification of Th17 cells. We found 23 SNPs associated with autoimmune diseases within Th17-enhancers that precisely overlapped with the binding sites of transcription factors actively engaged in T-cell functions. Among the Th17-specific enhancers, we identified an enhancer in the intron of RORA and demonstrated that this enhancer positively regulates RORA transcription. Moreover, CRISPR-Cas9-mediated deletion of a transcription factor binding site-rich region within the identified RORA enhancer confirmed its role in regulating RORA transcription. These findings provide profound insights into the potential mechanism by which the RORA enhancer orchestrates Th17 differentiation.